Failure analysis of two 3D embedded cracks in offshore pipelines at the welding joints - Hoo, Zhiong Sheng (Nanyang Technological University, 2022)
An offshore pipeline is commonly subjected to large plastic deformation and repetitive fluctuating loadings. It can be due to the installation processes or ocean waves. Inevitably, such loadings affect the cracks that exist in the offshore pipelines and cause material fractures. Incidents such as oil leakage due to fracture failure will bring detrimental impacts to the production, transportation capacity and global economy as well as the environment. In fact, such failures are predictable and could be avoided if research works are carried out to simulate the behaviours of multiple cracks when the pipeline is subjected to a large strain deformation to identify the fracture criteria. In addition, it is observed that lots of cataclysmic fracture failures of pipelines were associated with accelerated fatigue crack growth due to the coalescence of multiple cracks. Unfortunately, most of the published works only focused on a single crack’s behaviour. The prediction of the service life of pipelines due to the multiple cracks is still a challenging issue to deal with as there are still multiple parameters affecting the fatigue life of pipelines to be discovered and analysed. This project aims to study the elastic-plastic stress on two 3D interacting embedded elliptical cracks in offshore pipelines to investigate its fracture criteria and fatigue behaviour. The main methodology employed for analysing these interacting cracks’ behaviour is finite element method (FEM) with using an existing commercial software package, ANSYS. The mechanical properties and dimensions of offshore pipeline, formulation of the finite element modelling and geometrical configuration of the interacting cracks are explained in detail. Next, the effect of various parameters on the fracture resistance (CTOD) and fatigue crack growth rate are evaluated with the use of tabular and graphical data. It shows that the results obtained by FEM are reasonable and reliable. Two coplanar cracks can be seen as a single isolated crack provided the separation distance is sufficiently large as compared to the crack sizes.